BLACKENING OF CANNED PRAWN AND ITS PREVENTION - . NANDAKUMARAN, M; CHAUDHURI, D. R. CHAUDHURI; PILLAI, V K (Fishery Technology, 2025)
The paper gives an account of the types of blackening associated with canned prawn in brine and their control. It was found that blackening caused by iron sulphide could be controlled b):’ maintaining proper titratable acidity of fill brine in cans. The paper also elaborates on the factors responsible for or governing this criticaltitratable acidity. In regard to copper sulphide blackening, control was found to be difficult by maintaining the acidity or Â·by additives such as EDTA when the copper content in the material went above the critical level.